Inclusive growth: the contribution of service sector to employment in Malaysia - Hamid, Zarinah (IndianJournals.com, 2011)

(untitled)
This paper analyzes the role and significance of service sector in terms of its contribution to employment in Malaysia. It also discusses the goals of New Economic Policy (NEP) in restructuring the social fabric and employment patterns. A two-sector model is adopted to analyze the growth of service sector in Malaysia. The findings indicate that the rising income hypothesis component accounted the highest percentage change in the service share of employment (56.4 percent) followed by lagging productivity hypothesis component (39.5 percent). The former component indicates that rising income acts as the central cause of the movement of the Malaysian economy towards service industries, while the latter component reflects lagging performance of labour productivity in the service sector. The service sector takes a leading role in providing jobs for the Malaysians and by allowing as many members of the public to participate and contribute to the economic growth through employment opportunities, the concept of unity in diversity and inclusiveness among members of Malaysian society could be achieved.